Pengaruh Pendidikan Pancasila terhadap kesadaran hukum dan perilaku siswa SMP Studi di SMPNegeri 6 Moncongloe Maros - sinta angraini; Suardi; Auliah Andika Rukman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of Pancasila Education on the legal awareness and behavior of students at SMP Negeri 6 Moncongloe Maros. The research background is based on the importance of Pancasila Education as an effort to instill the nation’s fundamental values of justice, humanity, unity, democracy, and divinity in shaping the character and legal awareness of the younger generation. Field observations show that violations of school regulations such as bullying and truancy still occur frequently, indicating the need for a more contextual and varied implementation of Pancasila learning. The study employed a mixed-methods approach with a convergent parallel design, combining quantitative data (questionnaires administered to 97 students in grades VII–IX) and qualitative data (interviews with the principal, teachers, and selected students). Quantitative analysis used descriptive statistics, while qualitative analysis followed Miles and Huberman’s model. The instruments included a Pancasila values comprehension test, a legal awareness questionnaire, interview guidelines, and observation sheets. The results indicate that students’ understanding of Pancasila values is generally good, especially among ninth graders who are able to relate the meaning of the five principles to real-life actions. Pancasila Education positively influences the enhancement of legal awareness, as evidenced by a decrease in violations and an increase in discipline, honesty, responsibility, and student participation in Pancasila-based activities. Active learning approaches such as discussions and problem-based learning are more effective in shaping positive behavior compared to conventional methods. However, challenges remain, including the influence of the social environment, digital media, and limited variation in teaching methods. In conclusion, Pancasila Education has a strong impact on shaping students’ legal awareness and behavior in accordance with social and legal norms. Recommendations include strengthening teacher competence through training, innovating context-based learning methods tailored to students’ social environments, and integrating Pancasila values into all school activities to holistically shape student character.